Consider an n × n square matrix A such that A i j = min ( i , j ) 1 .
Let t n = t r ( A − 1 )
Find n = 1 ∑ ∞ ∣ t n ∣ + 1 1
Note: t r ( X ) denotes the trace i.e. the sum of the diagonal entries of the matrix X .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
i got it right but forgot to add 1/2 at the end. sad me
I was inspired to post this problem after seeing a similar problem that appeared in the Putnam Competition of 2014.
Log in to reply
Indeed. My solution already gives the answer to A2, since it is ( − 1 ) n F n ( 0 ) = n ! ( n − 1 ) ! ( − 1 ) n − 1 . By the end of "Trickier Trace", I have identified the inverse of A ( n ) as the symmetric tridiagonal matrix mentioned in passing in the Putnam solution.
Problem Loading...
Note Loading...
Set Loading...
Let A ( n ) be the n × n version of this matrix, and let F n ( t ) = d e t ( t I n − A ( n ) ) be the characteristic polynomial of the matrix A ( n ) . Then F 1 ( t ) = t − 1 and F 2 ( t ) = t 2 − 2 3 t − 2 1 . If n ≥ 3 we can use elementary row operations to show that F n ( t ) = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ − 1 − 1 − 2 1 − 2 1 t I n − 2 − A ( n − 2 ) ⋯ ⋯ ⋯ ⋯ − n − 2 1 − n − 2 1 − 1 − 2 1 ⋮ ⋮ − n − 2 1 t − n − 1 1 − n − 1 1 − 1 − 2 1 ⋮ ⋮ − n − 2 1 − n − 1 1 t − n 1 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ − 1 0 − 2 1 0 t I n − 2 − A ( n − 2 ) ⋯ ⋯ ⋯ ⋯ − n − 2 1 0 − 1 − 2 1 ⋮ ⋮ − n − 2 1 t − n − 1 1 − t − 1 − 2 1 ⋮ ⋮ − n − 2 1 − n − 1 1 t + n ( n + 1 ) 1 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = ( t + n ( n − 1 ) 1 ) ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ − 1 − 2 1 t I n − 2 − A ( n − 2 ) ⋯ ⋯ − n − 2 1 − 1 − 2 1 ⋮ ⋮ − n − 2 1 t − n − 1 1 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ + t ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ − 1 − 2 1 t I n − 2 − A ( n − 2 ) ⋯ ⋯ − n − 2 1 − 1 − 2 1 ⋮ ⋮ − n − 2 1 − n − 1 1 ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ ∣ = ( t + n ( n − 1 ) 1 ) F n − 1 ( t ) + t d e t B n − 1 ( t ) where B n − 1 ( t ) is the ( n − 1 ) × ( n − 1 ) matrix that only differs from t I n − 1 − A ( n − 1 ) by having − n − 1 1 , instead of t − n − 1 1 , as the bottom right element. In particular, then d e t B n − 1 ( 0 ) = d e t ( − A ( n − 1 ) ) = F n − 1 ( 0 ) . We thus obtain the recurrence relations F n ( 0 ) = n ( n − 1 ) 1 F n − 1 ( 0 ) F n ′ ( 0 ) = n ( n − 1 ) 1 F n − 1 ′ ( 0 ) + 2 F n − 1 ( 0 ) n ≥ 3 We can solve these recurrence relations to deduce that n ! ( n − 1 ) ! F n ( 0 ) = − 1 , n ! ( n − 1 ) ! F n ′ ( 0 ) = 1 − 3 2 ( n − 1 ) n ( n + 1 ) n ≥ 1
Since A ( n ) is a symmetric matrix, it is diagonalisable, and hence, if F n ( t ) = t n + a n − 1 t n − 1 + a n − 2 t n − 2 + ⋯ + a 1 t + a 0 then T r A ( n ) is just the sum of the eigenvalues of A ( n ) , and hence equal to − a n − 1 . The matrix A ( n ) − 1 is also symmetric, and its characteristic polynomial is the reverse of F n ( t ) , namely a 0 1 ( a 0 t n + a 1 t n − 1 + ⋯ + a n − 1 t + a n ) and hence we deduce that t n = T r A ( n ) − 1 = − a 0 a 1 = − F n ( 0 ) F n ′ ( 0 ) = 1 − 3 2 ( n − 1 ) n ( n + 1 ) n ≥ 1 and hence, finally, n = 1 ∑ ∞ ∣ t n ∣ + 1 1 = 2 1 + n = 2 ∑ ∞ 2 ( n − 1 ) n ( n + 1 ) 3 = 2 1 + 4 3 n = 2 ∑ ∞ ( ( n − 1 ) n 1 − n ( n + 1 ) 1 ) = 2 1 + 8 3 = 8 7
An alternative approach to calculating T r [ A ( n ) − 1 ] relies on obtaining an inductive formula for the inverse matrix A ( n ) − 1 . Note that ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ 0 0 A ( n ) − 1 ⋯ n ( n + 1 ) 0 ⋮ ⋮ 0 0 − n ( n + 1 ) ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ A ( n + 1 ) = ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ 0 0 A ( n ) − 1 ⋯ n ( n + 1 ) 0 ⋮ ⋮ 0 0 − n ( n + 1 ) ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ 1 A ( n ) 2 1 ⋯ ⋯ ⋮ n 1 1 2 1 ⋮ n 1 n + 1 1 ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ = ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ 0 0 I n ⋯ 0 0 0 0 ⋮ 0 1 1 ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ so that A ( n + 1 ) − 1 = ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ 0 0 I n ⋯ ⋯ 0 0 0 ⋮ 0 − 1 1 ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ 0 0 A ( n ) − 1 ⋯ 0 n ( n + 1 ) 0 ⋮ ⋮ 0 0 − n ( n + 1 ) ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ = ⎝ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎜ ⎛ 0 0 A ( n ) − 1 − n ( n + 1 ) K ( n ) ⋯ 0 n ( n + 1 ) 0 0 ⋮ 0 n ( n + 1 ) − n ( n + 1 ) ⎠ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎟ ⎞ where K ( n ) is the n × n matrix with zeros in all components except the bottom right one, which has the value 1 . From this it seems that A ( n ) − 1 is always a tridiagonal matrix, but we do not need to identify it orecisely. We see that T r [ A ( n + 1 ) − 1 ] = T r [ A ( n ) − 1 − n ( n + 1 ) K ( n ) ] − n ( n + 1 ) = T r [ A ( n ) − 1 ] − 2 n ( n + 1 ) n ≥ 1 and hence we deduce that T r [ A ( n ) − 1 ] = 1 − 2 r = 1 ∑ n − 1 r ( r + 1 ) = 1 − 3 2 ( n − 1 ) n ( n + 1 ) n ≥ 1